2019
DOI: 10.1038/s41467-019-09351-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant-inspired adhesive and tough hydrogel based on Ag-Lignin nanoparticles-triggered dynamic redox catechol chemistry

Abstract: Adhesive hydrogels have gained popularity in biomedical applications, however, traditional adhesive hydrogels often exhibit short-term adhesiveness, poor mechanical properties and lack of antibacterial ability. Here, a plant-inspired adhesive hydrogel has been developed based on Ag-Lignin nanoparticles (NPs)triggered dynamic redox catechol chemistry. Ag-Lignin NPs construct the dynamic catechol redox system, which creates long-lasting reductive-oxidative environment inner hydrogel networks. This redox system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
602
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 822 publications
(641 citation statements)
references
References 52 publications
11
602
0
Order By: Relevance
“…These explain the superior antibacterial performance of the present deign which combines the germ‐killing capability of the quinone group and the protonated amino group. On the other hand, unlike previous antibacterial hydrogels that were generally cell repellent, the hydrogel simultaneously exhibited good cytocompatibility due to catechol groups (cell affinity) on surface of the adhesive hydrogels 2b,26…”
Section: Resultsmentioning
confidence: 88%
“…These explain the superior antibacterial performance of the present deign which combines the germ‐killing capability of the quinone group and the protonated amino group. On the other hand, unlike previous antibacterial hydrogels that were generally cell repellent, the hydrogel simultaneously exhibited good cytocompatibility due to catechol groups (cell affinity) on surface of the adhesive hydrogels 2b,26…”
Section: Resultsmentioning
confidence: 88%
“…The frequency sweep results showed that storage modulus ( G ′) was greater than loss modulus ( G ″) over the entire frequency range (Figure S7A, Supporting Information), which is indicative of elastic‐like behavior. The increasing trend in the G ′ value is characteristic for SF@TA@HA composed entirely of intermolecular non‐covalent interactions . The dynamic nature of these bonding structures contributed to properties associated with shear‐thinning and subsequent recovery, which are important parameters for designing materials for minimally invasive tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds have a strong chelating ability with metal ions to form metal‐phenolic coordination bonds that endow metal‐phenolic materials with improved overall mechanical properties . In addition, phenolic compounds can also cross‐link with polymers such as proteins to assemble into hierarchical networks with appropriate water‐resistant adhesion performance, which mimics the adhesion mechanism of mussels . Thus, the collaborative self‐assembly mechanism of phenolic compounds offers the possibility to prepare a promising bone adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive hydrogels that can strongly adhere to wet tissues have been widely used in wound dressings, [1][2][3][4][5] hemostatic agents, [6][7][8][9][10] wearable devices, [11][12][13] drug delivery systems, 14,15 and tissue engineering, [16][17][18][19][20][21] owing to their strong adhesion, excellent biocompatibility, good permeability, high deformability, and tunable mechanical properties. Two main hydrogel design strategies have been adopted to achieve adhesion on wet tissues: adhering prefabricated adhesive hydrogels [22][23][24][25][26][27][28][29] on wet tissues and forming adhesive hydrogels on wet tissues in situ from precursor solutions.…”
Section: Introductionmentioning
confidence: 99%